Imagens e argumentos ecológicos nos livros didáticos : que educação ambiental é construída? - Bilthauer, Marisa Inês (2007)
This dissertation has as objective to analyze the analogies and metaphors of 12 books concerning Ecology and Ambient Education; 4 books from 1st to 4th series of the elementary school; 4 books from 5th to 8th also of the elementary school and 4 books from the secondary school. Methodologically we carry through the rhetorical examination of the subjects ecology and ambient education including illustrations gifts in those books. As conclusion we got: a) the metaphors harmony and balance of the nature confer to the analyzed collections of books wrong conceptions of ecosystem and environment; b) the metaphors population, community, the ecosystem notion, niche, habitat, net, web are reduced to the individual analogy, having contradicted the concept of ecology and ecosystem that deal with population and not individual dynamic.